MYC-induced apoptosis in mammary epithelial cells is associated with repression of lineage-specific gene signatures. Issue 3 (1st February 2016) - Haikala, Heidi M.; Klefström, Juha; Eilers, Martin; Wiese, Katrin E.
ABSTRACT: Apoptosis caused by deregulated MYC expression is a prototype example of intrinsic tumor suppression. However, it is still unclear how supraphysiological MYC expression levels engage specific sets of target genes to promote apoptosis. Recently, we demonstrated that repression of SRF target genes by MYC/MIZ1 complexes limits AKT-dependent survival signaling and contributes to apoptosis induction. Here we report that supraphysiological levels of MYC repress gene sets that include markers of basal-like breast cancer cells, but not luminal cancer cells, in a MIZ1-dependent manner. Furthermore, repressed genes are part of a conserved gene signature characterizing the basal subpopulation of both murine and human mammary gland. These repressed genes play a role in epithelium and mammary gland development and overlap with genes mediating cell adhesion and extracellular matrix organization. Strikingly, acute activation of oncogenic MYC in basal mammary epithelial cells is sufficient to induce luminal cell identity markers. We propose that supraphysiological MYC expression impacts on mammary epithelial cell identity by repressing lineage-specific target genes. Such abrupt cell identity switch could interfere with adhesion-dependent survival signaling and thus promote apoptosis in pre-malignant epithelial tissue.